Economic Exploitation of Children in The Urban Context: a Case Study of Palembang City - Hana Pertiwi; Atika Atika; Muhammad Abdillah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This article aims to examine children as victims often exploited in the social reality of society. The study is conducted to observe how children are utilized as instruments to meet economic needs, primarily by their parents. Additionally, this investigation seeks to examine, analyze the causative factors, and explore the implications resulting from economic exploitation of children. The approach in this paper is descriptive-qualitative, utilizing a library research method with readings and searches on the Google search engine related to "economic exploitation of children." The article reveals that children are positioned as tools to acquire resources for their parents. It also illustrates that socio-economic conditions often serve as a rationale for parents to exploit children economically, and this exploitation has persisted continuously amidst the growing demands for child protection. The study further demonstrates systematic and structured economic exploitation of children in Palembang City, frequently conducted openly. Such practices place children as vulnerable subjects within the legal framework, often neglecting the rights of children, as commonly observed in the social reality of the community.